Bacteriocin Detection from Whole Bacteria by Matrix-Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry - Hindré, Thomas (American Society for Microbiology, 2003)
Class I bacteriocins (lantibiotics) and class II bacteriocins are antimicrobial peptides secreted by gram-positive bacteria. Using two lantibiotics, lacticin 481 and nisin, and the class II bacteriocin coagulin, we showed that bacteriocins can be detected without any purification from whole producer bacteria grown on plates by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF-MS). When we compared the results of MALDI-TOF-MS performed with samples of whole cells and with samples of crude supernatants of liquid cultures, the former samples led to more efficient bacteriocin detection and required less handling. Nisin and lacticin 481 were both detected from a mixture of their producer strains, but such a mixture can yield additional signals. We used this method to determine the masses of two lacticin 481 variants, which confirmed at the peptide level the effect of mutations in the corresponding structural gene.